Children's rights, Eastern enlargement and the EU human rights regime - Iusmen, Ingi (European Policy Research Unit series., 2014)
This text critically examines how and why Eastern enlargement has impacted on EU human rights policy. By drawing on the EU's intervention in human rights provision in Romania before 2007, it is demonstrated that the feedback effects of this intervention have led to the emergence of an EU child rights policy.